2007
DOI: 10.2174/1874070700701010072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Practical Process Aspects for Lipozyme TL IM Catalyzed Bulk Fat Modification in a Batch Reactor

Abstract: A few issues to apply Lipozyme TL IM-catalyzed interesterification for bulk fat modification were investigated in a batch reactor system with concerning practical process development. The hydrolyzed products, i.e. free fatty acids and diglycerides, generated from the Lipozyme TL IM-catalyzed interesterification process due to water participation, can be minimized by enzyme pre-treatment. For the interesterified products, free fatty acids formed by hydrolysis had softening effect on solid fat content and diglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…After 24 h, the composition in the sn‐2 position was completely randomized and resembled the total composition. These results agree with those of Zhang 13 and Oh et al 15, who showed that optimization of the reaction time is very important if randomization in the sn‐2 position is to be controlled. A packed bed reactor rather than a batch reactor should be used if acyl migration is to be minimized, since the reaction times are much shorter 4, 18–20.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After 24 h, the composition in the sn‐2 position was completely randomized and resembled the total composition. These results agree with those of Zhang 13 and Oh et al 15, who showed that optimization of the reaction time is very important if randomization in the sn‐2 position is to be controlled. A packed bed reactor rather than a batch reactor should be used if acyl migration is to be minimized, since the reaction times are much shorter 4, 18–20.…”
Section: Resultssupporting
confidence: 91%
“…When water was present in the system the hydrolytic activity of the lipase improved, and the acyl enzyme could thus react with water, forming the hydrolysis product FFA. These two product groups will form simultaneously, and will do so until a steady‐state condition is reached, but at different rates depending on the enzyme load, the water content in the reaction mixture 13, the amount of enzyme preparation 14, and the reaction time 13. A small degree of hydrolysis is important at the beginning of the process to produce some DAG which can facilitate the production of new TAG, but uncontrolled hydrolysis will decrease the TAG yield.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the case of EDIE of PO, a further increase in the reaction time after U 3 TAG yield had reached its maximum resulted in a small but progressive increase in U 3 TAG yield. However, extended reaction time also led to the formation of a high amount of by-products, probably because of acyl migration, which is in agreement with the findings of Hamam and Budge (2010), Lee et al (2015) and Zhang (2007). The extended reaction time may also lead to randomisation of FA in the glycerol backbone (Zhang, 2007).…”
Section: Degree Of Three Parameters On Enzymatic Directed Interesterisupporting
confidence: 89%
“…Lipozyme TLIM lipase conditioning. Lipozyme TLIM lipase was chosen as the catalyst in this study as it is commonly used for the enzymatic IE reaction, is low-priced, of food grade and possesses high IE activity (Lee et al, 2015;Zhang, 2007). The Lipozyme TLIM lipase was pre-conditioned to eliminate extra moisture before the EDIE reaction was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…This could explain the difference observed among both immobilized lipases. In case of Lipozyme TL, although it is immobilized on silica gel, a hydrophilic material, its particle size range is bigger (250-1000 µm) and also the true density reported by Zhang et al (Zhang 2007) is high (1830 kg/m 3 ). Therefore, its surface area is considerably lower.…”
Section: Thermodynamic Aspects Of Sardine Oil Oxidationmentioning
confidence: 92%